MEWUJUDKAN SISTEM HUKUM INTEGRATIF - Al-Farabi (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2013)
The pluralism of law which is applying, that is Islamic law and customary law, has not found the related point to go to the integral law yet. It is because of till now in the Republic of Indonesia is using system of national law which based on several system of law that has a various pattern. That third systems of law are applying in Indonesia for a long time and dinamic. In early era, before colonialism, the relation of both addressed to pattern of integration with level of different coalescence in every sphere. The come of colonizer made a mark on the furthermore era with the pattern that reducted the applying law (Islam and custom) in Nusantara step by step till the top with applying a theory of reception. Furthermore, by reaching freedom, slowly the system of national law took role in developing and rearranged law in Nusantara, in other words, developing the theory of codification. To make that various law be able to be commander in living nationally and stately needs to be balanced the comprehension of national law which is integral. The mean of it in this writing is finite to the idea to see the system of national law like a law that makes a system of law of custom, Islam, and west as a source and reality of history which proportionates with the real experience of nation from early its existence till now, so that, to be national law, Islamic and customary laws are signed not to be incompatible with the philosophy of national law, and also, the system of national law ought to representate the value which lives and run by society.